2016
DOI: 10.1016/j.cryobiol.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Me 2 SO overexposure during cryopreservation on HOS TE85 and hMSC viability, growth and quality

Abstract: With the cell therapy industry continuing to grow, the ability to preserve clinical grade cells, including mesenchymal stem cells (MSCs), whilst retaining cell viability and function remains critical for the generation of off-the-shelf therapies. Cryopreservation of MSCs, using slow freezing, is an established process at lab scale. However, the cytotoxicity of cryoprotectants, like MeSO, raises questions about the impact of prolonged cell exposure to cryoprotectant at temperatures >0 °C during processing of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“… Assumption that data from sperm and embryos translated to somatic cells. Slow thawing – confounding of post thaw DMSO toxicity and slow thawing 36 , 37 . …”
Section: Discussionmentioning
confidence: 99%
“… Assumption that data from sperm and embryos translated to somatic cells. Slow thawing – confounding of post thaw DMSO toxicity and slow thawing 36 , 37 . …”
Section: Discussionmentioning
confidence: 99%
“…Currently, the existing cryopreservation methods for MSCs can be classified into two main categories, slow freezing and vitrification (rapid freezing) [ 10 ]. But both methods have some notable limitations [ 11 ], and there is an increasing amount of evidence showing the adverse effects of conventional cryopreservation methods for MSCs, such as the cytotoxicity of the standard cryoprotectant dimethyl sulfoxide (DMSO), cell apoptosis, cellular structure damages, and oxidative stress [ 12 14 ]. Recently, many approaches have been proposed for a more efficient application of cryopreserved MSCs, among which addition of selected agents in cryopreservation solution has shown good application prospects [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies with HepG2 cells suggested slow thawing up to -10°C, and then rapid thawing from -10°C to 4°C is beneficial due to the reduction of microfluctuations [39]. Finally, rapid thawing may not be beneficial due to the potential for increased toxicity of DMSO, especially if temperatures approach 37°C before wash-out [40]. An ideal thawing protocol for some cell types may consist of slow thawing to 4°C, followed by immediate dilution of cells in cold medium to reduce the toxic effects of DMSO prior to centrifugation.…”
Section: Discussionmentioning
confidence: 99%